Comparison of performance and characteristic of suberate, azelate and sebacate as PVC plasticizers - Nur Hafifah Nahdirah Jafri; Nor Hamidah Abu Othman; Mohd. Firdaus Mohamad Yusoff (Universiti Kebangsaan Malaysia, 2023)
Consumer’s health and safety problems that arise from using di (2-ethylhexyl) phthalate (DEHP) as a conventional plasticizer for PVC have led to the study of the production of alternative plasticizers based on dicarboxylate esters. In this study diester plasticizers based on suberic, azelaic and sebacic acid were synthesized with 2-ethylhexanol. PVC blends with these three diesters was conducted by solvent-casting technique. The characteristics of dicarboxylate esters plasticizers, which were judged to have excellent compatibility with PVC proved and evaluated by mechanical, thermal and migration stability test analyses as compared to DEHP. Improved tensile strength, elastic modulus, and elongation at break were observed in plasticized PVC films. Single peak of glass transition showed in all PVC-diester blends had lower range of temperatures, Tg (65.36°C - 71.90 °C). The first stage of maximum degradation temperature for PVC-D2EHSu, PVC-D2EHAz and PVC-D2EHSe films were recorded at 287.06 °C, 290.83 °C and 281.68 °C, respectively, which exhibited good thermal stability. The good compatibility between synthesized plasticizers and PVC proved that the dicarboxylate plasticizers able to replace DEHP and highly capable to use as either primary or secondary plasticizers in food packaging, medical devices and domestic appliances in polymer industry.